Medication overuse headache: a critical review of end points in recent follow-up studies - Hagen, Knut (Springer Milan, 2010)
No guidelines for performing and presenting the results of studies on patients with medication overuse headache (MOH) exist. The aim of this study was to review long-term outcome measures in follow-up studies published in 2006 or later. We included MOH studies with >6 months duration presenting a minimum of one predefined end point. In total, nine studies were identified. The 1,589 MOH patients (22% men) had an overall mean frequency of 25.3 headache days/month at baseline. Headache days/month at the end of follow-up was reported in six studies (mean 13.8 days/month). The decrease was more pronounced for studies including patients with migraine only (−14.6 days/month) compared to studies with the original diagnoses of migraine and tension-type headache (−9.2 days/month). Six studies reported relapse rate (mean of 26%) and/or responder rate (mean of 28%). Medication days/month and change in headache index at the end of follow-up were reported in only one and two of nine studies, respectively. The present review demonstrated a lack of uniform end points used in recently published follow-up studies. Guidelines for presenting follow-up data on MOH are needed and we propose end points such as headache days/month, medication days/month, relapse rate and responder rate defined as ≥50% reduction of headache frequency and/or headache index from baseline.